Mental Health Literacy and Mental Health Information-Seeking Behavior in Iranian University Students - Mahmoodi, Seyed Mohammad Hossein; Ahmadzad-Asl, Masoud; Eslami, Mohammad; Abdi, Mohadeseh; Hosseini Kahnamoui, Yasamin; Rasoulian, Maryam (Frontiers in Psychiatry, 2022)
Background: Inadequate Mental health literacy (MHL) is a problem worldwide. Research is limited in developing countries and about positive MHL. This study measured the disease-oriented MHL and positive MHL and investigated their association. In addition, this study explored the mental health information-seeking behavior among undergraduate students in Iran. Methods This study recruited undergraduate students of Tehran public universities through multistage stratified random sampling to undertake an analytical cross-sectional study. MHL was measured using Mental Health Literacy Scale (MHLS) and Mental Health Positive Knowledge (MHPK). Participants' most used mental health information sources and their trust in them were also inspected. Results A total of 543 students participated in this study. On average, the participants achieved about 65% of the total possible MHLS score, and 71% of participants showed sufficient MHPK score. The “internet” was the most used source for receiving and searching for mental health information. The most trusted source was “health care staff”. This study detected no correlation between disease-oriented MHL and positive MHL. Conclusions Mental health literacy of Iranian students still seems to be insufficient. As disease-oriented MHL and positive MHL were not correlated, specific educational interventions for each domain are needed. Although the internet is the main source of mental health knowledge, the trust of student in it is low. This issue should be taken into consideration in designing online educational interventions.